2008
DOI: 10.1111/j.1600-9657.2007.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of success in the reattachment of coronal fractures

Abstract: The aim of this study was to evaluate clinically and radiographically the restored teeth using reattachment technique of fractured fragment to the remaining tooth. This study was conducted on 11 children (six girls and five boys; age range: 8-13 years). Before the treatment, the teeth were evaluated clinically and radiographically. The broken incisal part was directly reattached to the remaining tooth part with flowable resin composite. Thereafter, with the purpose of obtaining optimal esthetics and function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 12 publications
1
80
2
5
Order By: Relevance
“…Moreover, the mean scores of parental-patient, satisfaction were reported as satisfied, very-satisfied. 15 The techniques described in this study are reasonably simple, while restoring function and esthetics with a very conservative approach. However, the professional has to keep in mind that a dry and clean working field and the proper use of bonding protocol and materials is the key for achieving success in adhesive dentistry.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the mean scores of parental-patient, satisfaction were reported as satisfied, very-satisfied. 15 The techniques described in this study are reasonably simple, while restoring function and esthetics with a very conservative approach. However, the professional has to keep in mind that a dry and clean working field and the proper use of bonding protocol and materials is the key for achieving success in adhesive dentistry.…”
Section: Discussionmentioning
confidence: 93%
“…A plethora of studies reported that fracture resistance of reattached tooth fragment can be improved with use of new adhesive agents, bonding materials and tooth preparation techniques techniques 14,15,16,17,18,19,20,21 . Apart from all these improvements, hydration of fragment also plays an important role in improving fracture resistance 9 .…”
Section: Discussion:-mentioning
confidence: 99%
“…In all cases, however, the authors agree that it is not possible to do without the use of a composite resin when there is loss of tooth structure and the absence of a perfect fit between the fragment and tooth remnant. Accordingly, in the case in question, the use of low viscosity resin was chosen for the reattachment per se, so as to obtain a cementation line of minimal thickness due to the ease of flow of this type of resin [11][12][13][14][15][16] . In those areas that require a greater volume of composite resin, such as with the filling of the pulp chamber and in the mesiobuccal portion, use is made of micro-hybrid composite resins.…”
Section: Discussionmentioning
confidence: 99%